New Horizons: Graduate Music Therapy Studies in Québec, Canada - Curtis, Sandi (Voices: A World Forum for Music Therapy, 2011)
The year 2011 marks the start of a new era for music therapy in the province of Québec with the official launch of its first and only graduate music therapy program. This program, situated at Concordia University in the heart of the city of Montréal, is described, along with its development, its purpose, its role in the changing landscape of music therapy in Québec, and its defining characteristics. Future ramifications for music therapy at Concordia University and in Québec and the rest of Canada are outlined.